Whiteness and the So-Called Problem of Preaching the Old Testament - Stark, David M. (Theology today, 2022)
This article explores the long-lamented problem of preaching the Old Testament in light of recent conversations about Whiteness in the Academy of Homiletics. Through an overview of the way the problem of the Old Testament is framed, I argue that Whiteness harmfully amplifies the quantity and severity of Old Testament problems encountered. Then, looking at several significant approaches to preaching the Old Testament, I argue that Whiteness contributes to a glaring neglect of power dynamics in solutions offered. Finally, I point to insights from many African American homileticians as a confrontation with Whiteness that offers a more fruitful foundation for an Old Testament homiletic.